Psychological condition of the elderly in the nursing home - Silvia, Efnida; Yarni, Linda (Universitas Negeri Yogyakarta, 2022)
Individuals who have good psychological conditions will commonly be able to create social relatedness and good moral feelings. The purpose of this study was to determine the social and moral feelings of the elderly in the Ikhwanus Shafa Lasi Mudo nursing home in Canduang District, Indonesia. This research used descriptive approach taking six key informants who are elderly residents aged 60 years and over, and the supporting informants consisted of two caregivers. The observation and interview results were analysed by reduction, presentation, verification, and comparison of the results. Specifically, this study focused on social feelings, sense of brotherhood, sympathy for friends who are in the orphanage environment, and sense of affection for others. It was found that in general, there showed a lack a sense of solidarity among others, a lack sense of help and respect. The elderly in this study informed that they developed such feelings that they are too close to the people in the orphanage compared to their family members. However, the moral feeling of the elderly has shown a good relationship between values and ethics (morals), where the elderly were able to take responsibility, feel guilty when violating norms, and feel at ease when obeying norms.